Carbon and oxygen dual-isotopes in tree rings indicate alternative physiological responses opted by European beech trees to survive drought stress. Issue 5 (17th November 2022) - Chakraborty, Tamalika; Reif, Albert; Matzarakis, Andreas; Helle, Gerhard; Faßnacht, Fabian; Saha, Somidh
ABSTRACT: Poor drought tolerance of European beech trees raised concerns in Europe. We hypothesized that beech could show an opposite physiological response to the same level of climatic drought with change in edaphic drought. We performed a combined analysis of δ 13 C and δ 18 O in tree rings to reveal retrospective temporal physiological responses of trees to drought. The edaphic drought was assessed by quantifying the capacity of soil to store water in plots (classified as "dry" and "less-dry") near the drought limit of the species in three near-natural oak-beech ecotones in Germany and Switzerland. Neighbourhood competition was quantified. A climatic drought index was calculated from meteorological records and related to the δ 13 C and δ 18 O values of the trees. Trees from dry plots showed a higher response to drought and climatic dependency than less-dry plots. Neighbourhood competetion increased δ 18 O values significantly. Dual isotope analysis shows a tendency of greater stomatal resistance in dry plots and higher stomatal conductance in less-dry plots. We conclude that beech trees belonging to the same population under changing soil water availability can show different physiological responses under climatic drought stress. Our finding indicates the high plasticity of the beech trees to survive drought stress with changing site conditions.